Penerapan Akuntansi Akrual di Instansi Pemerintah: Tinjauan Literatur dan Tantangannya di Indonesia - Aulia Norlaisa Dewi; Monika Handayani (P3M Politeknik Negeri Banjarmasin, 2025)
This research explores the implementation of accrual-based accounting in Indonesian government agencies and identifies the challenges encountered. Driven by the demands for reform in state financial management emphasizing transparency and accountability, this study employs a literature review methodology, analyzing various relevant sources. The findings indicate that accrual accounting enhances the quality of financial reports, supports data-driven decision-making, and strengthens public financial governance. However, significant obstacles persist, particularly regarding limited human resources, uneven information technology infrastructure, and disparities between central and regional government entities. This study recommends improving technical capacity, refining information systems, and strengthening cross-institutional coordination. The implications highlight the importance of an integrated approach focusing not only on regulation but also on resource readiness and supporting systems, to truly establish accrual accounting as a foundation for modern, transparent, and sustainable state financial governance.